2014
DOI: 10.1371/journal.pone.0087134
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Rescue and Inhibition Studies to Determine the Role of Arg301 in Phosphite Dehydrogenase

Abstract: Phosphite dehydrogenase (PTDH) catalyzes the NAD+-dependent oxidation of phosphite to phosphate. This reaction requires the deprotonation of a water nucleophile for attack on phosphite. A crystal structure was recently solved that identified Arg301 as a potential base given its proximity and orientation to the substrates and a water molecule within the active site. Mutants of this residue showed its importance for efficient catalysis, with about a 100-fold loss in k cat and substantially increased K m,phosphit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
1
14
2
Order By: Relevance
“…We observed that the R535A mutant losses its activity to a greater extent than does the wild-type protein at the same hydrazine concentration ( Fig 3C ), a possible result of the lack of hydrogen bond formation caused by the missing guanidinium group in R535A. Interestingly, a similar phenomenon was observed in studies with phosphite dehydrogenase, in which the side chain of Arg301, protruding towards the active site, plays a crucial role in forming the phosphite binding entrance via water molecule mediated hydrogen bonding to Trp134 [ 50 ]. Likewise, other enzymes also utilize the arginine side chain for proper substrate binding [ 48 , 53 – 57 ].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We observed that the R535A mutant losses its activity to a greater extent than does the wild-type protein at the same hydrazine concentration ( Fig 3C ), a possible result of the lack of hydrogen bond formation caused by the missing guanidinium group in R535A. Interestingly, a similar phenomenon was observed in studies with phosphite dehydrogenase, in which the side chain of Arg301, protruding towards the active site, plays a crucial role in forming the phosphite binding entrance via water molecule mediated hydrogen bonding to Trp134 [ 50 ]. Likewise, other enzymes also utilize the arginine side chain for proper substrate binding [ 48 , 53 – 57 ].…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies with carboxypeptidase, E . coli ornithine transcarbamylase, asparagine synthetase B, alkanesulfonate monooxygenase and phosphite dyhedrogenase have identified the participation of arginine in enzymatic catalysis by showing the existence of exogenous guanidine mediated activity restoration corresponding to an enhancement in k cat [ 34 , 47 50 ]. Among these, the respective R57G and R325A mutants of ornithine transcarbamylase and asparagine synthetase B also displayed preferences for rate enhancements (10% and 15%, respectively) by guanidine hydrochloride over other guanidinium based agents, which is similar to that of hcAMPP ( Fig 3B ) [ 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search for similar structures within the PDB using the server DALI 16 reveals that the secondary structure of GRHPR (of PfuGRHPR as well as PyaGRHPR) shares significant similarity with phosphite dehydrogenase (PTDH) especially with PTDH from Pseudomonas stutzeri 17 18 (PDB ID Code: 4E5N (binary complex) and 4E5K (ternary complex)). Indeed, the superposition of PstPTDH (4E5K) with PfuGRHPR or PyaGRHPR gives RMSD values of 1.32 Å and 1.29 Å with sequence identity only close to 34%.…”
Section: Resultsmentioning
confidence: 99%
“…In PfuGRHPR structure, this interaction is obviously abolished with glyoxylate. Despite a different substrate, phosphite dehydrogenase (PTDH) possesses a high structural similarity with GRHPR and the active-site residues are strictly conserved 17 18 . In PTDH, systematic mutations of the three residues composing the network (Arg297, Ser291 and Trp138) show a clear effect on substrate affinity 20 .…”
Section: Discussionmentioning
confidence: 99%